Human Identity and Agency Envisioned by Moral Imagination in the Practice of the Self - Putranto, I. Eddy (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2009)
In the information-saturated culture today identity of the self is getting blurred and pulverized. The situation is disorienting and calling into question the concept of ‘identity’, ‘selfhood’, ‘subject’ or ‘authenticity’. Despite various kinds of method of ‘self-mastery’, the self remains elusive, even more than ever before. This article discusses the problem of ‘self’, not in terms of its ‘essence’, but rather in terms of what s/he does in the practice of the self. Identity is something constructed by the act of searching for meaning. Through ‘moral imagination’, the search for meaning becomes moral responses toward events of humanity. Self is the subject of history that actualizes him/herself through the history of humanity.